THE ILLOCUTIONARY ACT FOUND IN SHOTGUN BOY ENGLISH WEBTOON - A. A. Ayu Made Dwiari; I Nyoman Kardana; I Ketut Subagia (Universitas Warmadewa, 2026)
The title of this research is “The Illocutionary Acts Found in Shotgun Boy English Webtoon.” The purpose of this research is to classify the types and identify the functions of illocutionary acts based on Searle’s theory. Qualitative descriptive approach was applied in this research. The data source of this research is a webtoon entitled Shotgun Boy, and the data were collected from the utterances that contain illocutionary acts. In collecting the data, the researcher used observation and note-taking methods. The steps to collect the data in this research included downloading the Webtoon app, reading the entire Webtoon, determining the utterances that present illocutionary acts, classifying them based on Searle’s five types of illocutionary acts, and identifying the functions of each type. The research result was described descriptively and presented using an informal method. The result of this research shows the use of five types of illocutionary acts, which are assertives, directives, commissives, expressives, and declaratives. In addition, each type has several functions such as stating belief, getting someone to do something, committing to something, expressing feelings, and declaring a status or change.